Exploring the dynamics of inflation, unemployment, and economic growth in Somalia: a VECM analysis - Abdisalan Aden Mohamed; Abdikafi Hassan Abdi (Cogent Economics & Finance, 2024)
Maintaining optimal levels of unemployment and external debt remains a significant challenge for ensuring consistent economic growth in many developing countries. Despite persistent economic difficulties marked by political instability, high unemployment, external debt, inflation, and limited capital formation, Somalia is increasingly recognizing the importance of fostering stability, instituting economic reforms, seeking debt relief through international collaborations, and promoting inclusive growth. Therefore, this paper empirically examines the relationship between gross domestic product (GDP), unemployment, external debt, inflation, and gross capital formation in Somalia using annual data from 1991 to 2021. To attain the aim of the study, we implemented the Augmented Dickey-Fuller (ADF), vector error correction model (VECM), variance decomposition, impulse response function, and Granger causality test. The outcomes of the study present a negative relationship between unemployment and economic growth, implying the applicability of Okun’s law in Somalia. This suggests that the unemployment crisis in Somalia can be attributed to a lack of economic growth. Furthermore, the study identified that economic growth is negatively associated with inflation and external debt. Moreover, the study reveals unidirectional links between unemployment and GDP, gross capital formation and GDP, GDP and external debt, CPI and GDP, unemployment and gross capital formation, and external debt and unemployment. No causal effects were found in the other combinations of interactions. To sustain economic growth and job creation, the government must implement effective fiscal policies, create an inviting atmosphere, and have a flexible labour market policy to encourage the private sector and small businesses.